Poorest in the West: Probing Haiti’s Image in the Wake of the 2008 Hurricane Season - Cooke, Elizabeth (Consilience, 2010)
In the fall of 2008, Haiti was hit by a series of tropical storms that caused widespread flooding, hundreds of deaths, and costly damage to farm fields, roads, and buildings. Although a portion of the destruction is attributable to the vagaries of nature, the extent of the devastation and the frequency of such events in Haiti lead to deeper questions about the history of environmental degradation and the failure of development efforts in the country. Internal corruption and external profiteering have each played a role in the country’s economic and environmental collapse since its independence over 200 years ago. Currently, most investors have been scared away by Haiti’s precarious political state while many non-profit organizations have adopted a narrow focus on surface issues. The failure to address the root causes of environmental destruction in Haiti has resulted in repeated disasters that destroy any development progress made during the intervening years. This report examines Haiti’s past and future in light of the author’s experiences in Gonaives during the 2008 hurricane season. It also introduces the work of two organizations—one non-profit and one for-profit—that are striving to reshape Haiti’s image through integrated economic and environmental reforms.